2020
DOI: 10.1093/rheumatology/keaa021
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of immunoassays to detect autoantibodies in patients with myositis is dependent on autoantibody specificity

Abstract: Objectives In order to address the reliability of commercial assays to identify myositis-specific and -associated autoantibodies, we aimed to compare the results of two commercial immunoassays with the results obtained by protein immunoprecipitation. Methods Autoantibody status was determined using radio-labelled protein immunoprecipitation for patients referred to our laboratory for myositis autoantibody characterization. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 19 publications
5
84
1
Order By: Relevance
“…In this study, the ANA titer was low (<1:80) in half of the patients with anti-NXP2 Antibody. This result suggested that the anti-NXP2 antibody titer was relatively low, which may explained that the sensitivity of a commercial blot assay kit for detecting anti-NXP2 antibody was low in a previous report (15).…”
Section: Discussionmentioning
confidence: 71%
“…In this study, the ANA titer was low (<1:80) in half of the patients with anti-NXP2 Antibody. This result suggested that the anti-NXP2 antibody titer was relatively low, which may explained that the sensitivity of a commercial blot assay kit for detecting anti-NXP2 antibody was low in a previous report (15).…”
Section: Discussionmentioning
confidence: 71%
“…While it would have been useful to identify groups with similar muscle disease activities over time, there were too many missing CMAS values to do so. Although 96% of our autoantibody data were generated using the same method, inconsistent testing methods are a challenge for combining data [ 33 , 34 ]. Future work could investigate how medication exposure both influences and is influenced by disease trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…These clinically available MSA testing methodologies utilize differing techniques for MSA detection, with the OMRF profile determined predominantly by immunoprecipitation and immunoblotting and the Myomarker Panel 3 by enzyme immunoassay (EIA). While a direct comparison of test performance characteristics between these 2 methodologies has not been published for reference, it has been noted that EIA methodology has a lower sensitivity for detection of some autoantibodies, such as anti-transcription intermediary factor 1γ (anti-TIF1γ), while also potentially leading to more false-positive results (16)(17)(18)(19).…”
Section: Sample Acquisition and Clinical Data Collectionmentioning
confidence: 99%